Prospective Study of Endogenous Hormones and Incidence of Venous Thromboembolism: The Atherosclerosis Risk in Communities Study - Roetker, Nicholas S.; MacLehose, Richard F.; Hoogeveen, Ron C.; Ballantyne, Christie M.; Basu, Saonli; Cushman, Mary; Folsom, Aaron R. (Thrombosis and Haemostasis, 2018)
Exogenous hormone treatments in women (oral contraceptives and hormone replacement therapy [HRT]) are established risk factors for venous thromboembolism (VTE), but less is known about associations between plasma levels of endogenous hormones and VTE risk. We examined the association of baseline dehydroepiandrosterone sulphate (DHEAS), testosterone and sex hormone-binding globulin (SHBG) with risk of future VTE in men and post-menopausal women in the Atherosclerosis Risk in Communities Study. Testosterone, DHEAS and SHBG were measured in plasma samples collected in 1996 to 1998. Cox proportional hazards models were used to estimate hazard ratios for incident VTE adjusting for age, race/ethnicity, body mass index, height, smoking, estimated glomerular filtration rate and C-reactive protein. All analyses were stratified by sex and by current HRT use in women. Among 3,051 non-HRT-using women, 1,414 HRT-using women and 3,925 men at risk at baseline, 184, 62 and 206 experienced incident VTE after a median follow-up of 17.6 years. Plasma hormones were not associated with incidence of VTE among men and non-HRT-using women, although lower plasma DHEAS, when modelled using quartiles or restricted cubic splines, was associated with higher risk of VTE among HRT-using women. This study does not support the existence of an important association between plasma concentrations of endogenous testosterone, DHEAS or SHBG with risk of VTE in middle-aged to older men or post-menopausal women not using HRT.
Keywords: deep vein thrombosis; pulmonary embolism; epidemiologic studies; risk factors; hormones